The Implementasi Total Quality Management (TQM) di SD Al-Hikmah Surabaya - Ulfatur Rahmah (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2018)
This research aims to analyze and explain the key factors contributing on successful implementation of total quality management in Al-Hikmah Primary School of Surabaya. The sustainability of total quality management in Al-Hikmah Elementary School is proven by the increasing number of students’ enrolment which exceeded the fixed quota; the high level of teachers and students achievement; as well as the big number of competitive graduates. Using qualitative descriptive approach, this research finds that successful implementation of total quality management is highly dependent on top-down leadership system of the school, effective communication among stakeholders, the properly measured reward and punishment to students, and the continous internal and external assessment of educational quality management.